School of aerospace, transport and manufacturing safety and accident investigation - Fraisacher, Thomas M. (Cranfield University, 2022)
The airline pilot’s profession is a highly challenging and ever-changing environment requiring constant safety-related decisions made by the pilots themselves to ensure the high standards of the aviation safety system. In an otherwise highly regulated European aviation safety system, the effects of “pilot commuting” remain a potential blind spot, even though commuting and its consequences are representing a risk for the safety of the European air transport system. This research explores commuting stress, pilot performance, locus of control, turnover intention and safety behaviour in connection to the European pilot commuting process. Variables involved in the commuting process are established and analysed. A Europe- wide airline pilot study sent out to over 15,000 European airline pilots resulted in 1,461 usable questionnaires to examine European airline pilot commuting data for the first- time. Statistical analysis reveals that commuting is a standard behaviour of many European pilots. More than half of the European airline pilots declared themselves as active commuters by the definition of this research. The statistical analyses are based on structural equation modelling and partial least square (PLS)-structural equation modelling (SEM). These analyses reveal the interaction of commuting stress, turnover intention, locus of control, safety behaviour and resulting professional pilot performance. A predictive model has been developed which explains mediating and moderating effects on respective variables. The findings shed new light on the professional pilot performance of commuter, non-commuter and intermediate housing commuter pilots in Europe. Which were in contrast with what was anticipated from the research literature. This research identified a significant predictability and interaction between commuting stress, safety behaviour, and turnover intention. It also highlights that locus of control has a predictive quality regarding commuting stress. Applying the theoretical framework of Sloan and Cooper (1986) on pilot performance and the maximum adaptation model (Hancock and Warm, 2003), a new European airline pilot commuting model using PLS-SEM predictive qualities was developed. This research allows a deep insight into commuting risks in terms of optimal pilot commuting distances and times and resulting pilot performance. It offers an important and, until now, neglected contribution to the European aviation safety system. A comparative three-group analysis observed that non-commuters exhibited the lowest stress levels, while commuters experienced moderate stress due to commuting. Pilots who used intermediate housing facilities reported the highest stress levels among the three groups. Moreover, the analysis revealed that European airline pilots engaged in commuting exhibited significantly better subjective performance when compared to their non-commuting counterparts. Furthermore, the results indicate that commuters who utilize intermediate housing exhibit a significantly increased tendency to deviate from standard procedures on an individual basis, likely due to their unique commuting needs. This model presents a foundation for innovating and implementing new strategies in managing European airline pilot commuting, duty scheduling, and base assignments, suggesting a positive direction for change based on these research findings.
Mayer, Robert - Associate Supervisor
Keywords: pilot commuting; pilot performance; occupational commuting; commuting stress; locus of control; turnover intention; safety behaviour